KESESUAIAN PENGELOLAAN DAN GAMBARAN PENGGUNAAN LOGISTIK FARMASI TROLI DI RUANG ICU RSUD ULIN BANJARMASIN - Amaliyah Wahyuni; Alifa Husnul Khotimah (Jurnal Insan Farmasi Indonesia, 2020)
Emergency medicine is life saving, so emergency management is important to improve emergency services. The implementation of emergency pharmaceutical logistics management must use an effective, coordinated and multidisciplinary process. The purpose of this study was to determine the percentage of suitability of emergency trolley management and the type of emergency pharmacy logistics with the highest frequency percentage of using emergency trolleys in the ICU room of RSUD Ulin Banjarmasin. This research is a non-experimental descriptive study, data were collected prospectively using observation sheets based on SPO and use sheets for emergency pharmacy logistics in the ICU room at RSUD Ulin Banjarmasin. The population and sample of this study were all observation data of emergency trolley management in the ICU Room. The sampling technique used is saturated sampling technique all populations as samples. Data analysis was performed by calculating the percentage of suitability and the data were presented in tabular form. The results showed that the overall percentage of suitability for emergency trolley on SPO was 43.4% and 56.6% unsuitable. The highest frequency of use of emergency drugs was Vascon (norefinephrine) 73.33%, while the highest medical equipment was at Surflo 20,22,24 86.67% and Spuit NGT 50cc / Spuit 50cc 86.67%.